1999
DOI: 10.1677/joe.0.1620167
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic expression of epidermal growth factor and keratinocyte growth factor in beta-cells results in substantial morphological changes

Abstract: The upregulation of a limited number of growth factors in our interferon-transgenic model for regeneration within the pancreas lead us to propose that these factors are important during pancreatic regeneration. In this study, we have assessed the influence of two growth factors within the pancreas, epidermal growth factor (EGF) and keratinocyte growth factor (KGF), by ectopically expressing these proteins under the control of the human insulin promoter in transgenic mice. This -cell-targeted expression of eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…Also in agreement with our previous results is the lack of pathological alterations in PIP-hBTC transgenic mice. This is in contrast to the multiple pathological effects including islet disaggregation, fibrosis, and even ductal metaplasia observed in transgenic mice with -cell-specific overexpression of the EGFR ligands EGF (Krakowski et al 1999) and heparin-binding EGF (Means et al 2003). This observation indicates that BTC has unique actions on pancreatic islets as compared to other EGFR ligands.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Also in agreement with our previous results is the lack of pathological alterations in PIP-hBTC transgenic mice. This is in contrast to the multiple pathological effects including islet disaggregation, fibrosis, and even ductal metaplasia observed in transgenic mice with -cell-specific overexpression of the EGFR ligands EGF (Krakowski et al 1999) and heparin-binding EGF (Means et al 2003). This observation indicates that BTC has unique actions on pancreatic islets as compared to other EGFR ligands.…”
Section: Discussionmentioning
confidence: 82%
“…The rat (Dahl et al 1996;Hanahan 1985;Vasavada et al 1996), mouse (Hara et al 2003), and human (Hotta et al 1998;Krakowski et al 1999) insulin promoters have been frequently used to direct expression of oncogenes, hormones, growth factors, transcription factors, reporter genes, and more recently of the enzyme Cre recombinase (Ahlgren et al 1998;Dor et al 2004;Gannon et al 2000;Postic et al 1999) specifically to pancreatic -cells in transgenic mice. A major caveat of the rat insulin promoter, however, is the reported ectopic expression in certain areas of the brain, potentially resulting in phenotypes in both -cells and neural cells (Gannon et al 2000;Martin et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of this growth factor and its receptors is up-regulated in pancreatic carcinomas [17]. Studies in transgenic mice expressing KGF alone [18] or both KGF and EGF [19] in their beta cells showed that ectopic expression of KGF in the pancreas induces increased ductal-cell proliferation, profound changes in pancreatic morphology and the appearance of hepatocytes within the Fig. 4A, B.…”
Section: Effect Of Kgf On Beta Cell and Ductal Cell Proliferationmentioning
confidence: 97%
“…Interestingly, studies on isolated islets suggest that EGF ligands have little mitogenic effect in culture (Sjoholm 1996). However, in vivo b-cell-specific overexpression of EGF leads to increased b-cell proliferation (Krakowski et al 1999). These contrasting effects may reflect a differential response of the islet to the microenvironment.…”
Section: Introductionmentioning
confidence: 99%